On fractal dimensions of soil radon gas time series. (January 2022) - Rafique, Muhammad; Iqbal, Javid; Ali Shah, Syed Ahsin; Alam, Aftab; Javed Lone, Kashif; Barkat, Adnan; Ali Shah, Muhammad; Ahmad Qureshi, Shahzad; Nikolopoulos, Dimitrios
Abstract: This paper investigates the complexity of soil radon time series (RTS) recorded from March 2017 to April 2018 in Pakistan via RTM 1688-2 monitor, in direct linkage to parallel series of temperature, relative humidity, and pressure. Several complexity measures are employed. The normalized Lempel Ziv Complexity (LZC) of the complete RTS is 0.30 and 0.14, 0.22, and 0.14 for the complete time series of temperature, relative humidity and pressure respectively. LZC ranges between 0.3 and 0.5 for RTS and between 0.1 and 0.3 for temperature (T), relative humidity (RH) and pressure (P). Hurst exponent (HE) values via rescaled range (R/S) analysis show an inverse relationship with LZC. HE ranges between 0.60 ≤ HE ≤ 0.98 for RTS, 0.60 ≤ HE ≤ 0.92 for T series, 0.61 ≤ HE ≤ 0.93 for RH series, and 0.87 ≤ HE ≤ 0.98 for P series. Permutation Entropy (PE) is 1.7809 for complete RTS with a minimum of 1.7668 in August 2018. Highest value of Sample Entropy (SE) is 1.3716 for February 2018. The highest symbolic Normalized Corrected Shannon Entropy (NCSE) value is found in January 2018 with a value of 0.7864. Finally, the Fractal Dimensions varied significantly for calculation with the Sevcik's, Higuchi's and Katz's methods. Common dates of below threshold areas are reported. The different aspects of the derived results are discussed. Graphical abstract: Image 1 Highlights: Complexity, Hurst exponents and fractal dimensions of soil radon (RTS) in Pakistan. Normalized LZC are between 0.3 and 0.5 and Hurst exponents between 0.60 ≤ HE ≤ 0.9. HE show inverse relationship with LZC. Minimum Permutation Entropy was 1.7668 on August 2018, maximum Sample Entropy was 1.3716 on February 2018. Common dates of minimum fractal dimensions via Sevcik's, Higuchi's and Katz's methods are reported.